Can tourists become disciples? The formation and mechanism of place conversion in traditional Chinese villages - Xu, Luyao; Shi, Lei; Wang, Xin; Wan, Yuliang; Fan, Zhuo (Frontiers in Psychology, 2023)
Place attachment has been extensively studied in the field of tourism. However, it is important to recognize that place attachment alone may not fully capture the emotional expression of tourists’ spiritual beliefs and their sense of belonging to a destination. Therefore, a more comprehensive attachment theory is needed to encompass higher dimensions. This article focuses on the ancient Chinese villages of Yantou, Cangpo, and Furong from a tourist perspective, and introduces genius loci in architectural phenomenology. We set out to expand the study of spiritual dimensions of place attachment on the basis of local attachment, redefining tourists’ place connection and putting forward the new concept of place conversion. A qualitative analysis of online text using Rooting theory was conducted to condense 22 categories into 6 main categories and establish a model. The study shows that the mechanism of place conversion is composed of situational perception (place perception and place identity), physical and mental immersion (spatio-temporal immersion and place conversion), and behavioral willingness (tourists intention and conversion behavior). The study has implications for the conservation and development of traditional villages and future research on the spiritual experiences of tourists.